Maternal behavior in providing sweet foods and beverages to toddlers: A case study in Jembrana, Bali - Dewi, Ni Made Putri Kusuma; Prabandari, Yayi Suryo (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to explore maternal behavior in providing sweet foods and beverages to toddlers in Jembrana, Bali. Method: A qualitative case study design was employed, guided by the Health Belief Model to structure data collection and analysis. Twenty participants, including mothers of toddlers and health workers, were selected using purposive sampling from two primary health centers. Data were collected through in-depth interviews and analyzed using qualitative content analysis supported by NVivo 12 Plus. Results: Maternal behavior varied in the frequency and types of sweet food and beverage provision, often influenced by perceptions of susceptibility, seriousness, benefits, and barriers. Some mothers showed low perceived susceptibility, believing their children were not at risk, while others recognized the negative health impacts. Perceived benefits included preventing illness and controlling eating habits, while barriers included limited supervision and environmental influences. Family communication, social media, and personal experiences shaped cues to action. Conclusion: Maternal behavior in feeding toddlers sweet foods and beverages is shaped by a combination of personal perceptions, family dynamics, and environmental context. Efforts to promote healthier feeding practices should address these multifaceted influences through community-based education and supportive family engagement.